FACTORS AFFECTING OPERATING CASH FLOW TO STOCK RETURN THROUGH STOCK PRICE - Santoso, Aprih . (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract : Companies need funds in order to carry out operations such as the financing of production activities, pay employees, pay other expenses related to the operation of the company. One way to obtain these funds is to attract investors to invest in companies in the form of stock, but in making this investment is certainly not easy for investors, because investors need consideration beforehand to find out how the company's performance. The purpose of this study was to examine and analyze the effect of operating cash flow to stock return through stock price at companies listed on the Stock Exchange Year 2012-2015. The data used in this study dala are secondary data from the financial statements of companies listed on the Indonesia Stock Exchange period 2012 - 2015. The data are in the form of financial statements can be obtained from the Indonesian Capital Market Directory (ICMD), the IDX website www.idx.co. id as well as from various other sources to support this research. The population in this research is manufacturing companies listed on the Stock Exchange the period 2012 - 2015. The samples taken by the sampling technique used purposive sampling.From the test results and analysis of the data it can be concluded that operating cash flow directly and indirectly has no effect on stock returns through stock prices showed no significant results.Â Keywords : Â Operating Cash Flow, Stock Price, Stocks Return